To simplify the expression \( (125x^{7/3})^{-1/3} \), we can follow these steps:
-
Apply the negative exponent rule: \( a^{-n} = \frac{1}{a^n} \). So: \[ (125x^{7/3})^{-1/3} = \frac{1}{(125x^{7/3})^{1/3}} \]
-
Now simplify the expression inside the denominator: \[ (125x^{7/3})^{1/3} = 125^{1/3} \cdot (x^{7/3})^{1/3} \]
-
Calculate \( 125^{1/3} \): \[ 125^{1/3} = 5 \]
-
Simplify \( (x^{7/3})^{1/3} \) using the property \( (a^{m})^{n} = a^{mn} \): \[ (x^{7/3})^{1/3} = x^{(7/3) \cdot (1/3)} = x^{7/9} \]
-
So we have: \[ (125x^{7/3})^{1/3} = 5x^{7/9} \]
-
Putting it all together, we find: \[ (125x^{7/3})^{-1/3} = \frac{1}{5x^{7/9}} \]
Thus, the expression simplifies to \( \frac{1}{5x^{7/9}} \).
The answer that matches our result is:
c \( \frac{1}{5x^{7/9}} \)